Chemical binding of inorganic flame retardant compositions to polyamide fibers - Krival', Денис; Reva, Ольга (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
The investigation of the dependence of the strength of binding of inorganic non-toxic flame retardant compositions to the surface of polyamide fibres on the conditions of step impregnation processing. A method of chemical binding of inorganic modifier to the polyamide, the composition of the etching solutions, providing the fixation of the maximum amount of flame retardant on polyamide fiber.